Factors underlying elevated troponin I levels following pacemaker primo-implantation - Hnatek, Tomas; Taborsky, Milos; Maly, Martin; Kamenik, Libor; Littnerova, Simona; Sedlon, Pavel; Luxova, Jana; Fiserova, Marta; Pospisilova, Lenka; Hamouzova, Sarka; Danek, Josef; Zavoral, Miroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND: Cardiac troponins are routinely used as markers of myocardial damage. Originally, they were only intended for use in diagnosing acute coronary syndromes; however, we now know that raised serum troponin levels are not always caused by ischemia. There are many other clinical conditions that cause damage to cardiomyocytes, leading to raised levels of troponin. However, the specificity of cardiac troponins towards the myocardium is absolute. Our work focuses on mechanical damage to the myocardium and on monitoring the factors that raise the levels of cardiospecific markers after primo-implantation of a pacemaker with an actively fixed electrode. AIMS: (i) To determine whether the use of a primo-implanted pacemaker with an electrode system with active fixation will raise troponin levels over baseline. (ii) To assess whether troponin I elevation is dependent on procedure complexity. METHODS: We enrolled 219 consecutive patients indicated for pacemaker primo-implantation; cardiospecific marker values (troponin I, CKMB, myoglobin) were determined before the implantation procedure and again at 6- and 18-h intervals after the procedure. We monitored duration of cardiac skiascopy, number of attempts to place the electrode (active penetration into the tissue) and intervention range (single-chamber versus dual-chamber pacing), and we assessed the clinical data. RESULTS: The average age of the enrolled patients was 78.2 ± 8.0 years (median age, 80 years); women constituted 45% of the group. We implanted 128 dual-chamber and 91 single-chamber devices with an average skiascopic time of 38.6 ± 22.0 s (median, 33.5 s). Troponin I serum levels increased from an initial 0.03 ± 0.07 μg/L (median, 0.01) to 0.18 ± 0.17 μg/L (median, 0.13) and 0.09 ± 0.18 μg/L (median, 0.04) at 6 and 18 h, respectively. The differences were statistically significant (P < 0.001 or P < 0.001). We confirmed a correlation between troponin increase and duration of skiascopy (P < 0.001). We also demonstrated a correlation between increased troponin I and number of attempts to place a pacemaker electrode (penetration into the tissue) at 6 h (P < 0.001) post-implantation. CONCLUSION: We detected slightly elevated troponin I levels in patients with primo-implanted pacemakers using electrodes with active fixation. We demonstrated a direct correlation between myocardial damage (number of electrode penetrations into the myocardium) and troponin I elevation, as well as between complexity (severity) of the implantation procedure (indicated by prolonged skiascopy) and raised troponin I. The described phenomenon demonstrates the loss of the diagnostic role of troponin I early after pacemaker primo-implantation in patients with concomitant chest pain.
Keywords: srdeční arytmie; kreatinkinasa, forma MB; troponin; senioři nad 80 let; Prosthesis Implantation; Humans; lidé; troponin I; kardiostimulátor; myoglobin; Aged, 80 and over; cardiac pacing; Female; Male; Myoglobin; primo-implantation; Arrhythmias, Cardiac; Biomarkers; mužské pohlaví; Aged; Electrodes, Implanted; implantované elektrody; myocardial damage; ženské pohlaví; Postoperative Complications; Creatine Kinase, MB Form; Troponin I; biologické markery; Pacemaker, Artificial; implantace protézy; pooperační komplikace; senioři